PalMod 130k marine palaeoclimate data synthesis version 1.1.1 - Jonkers, Lukas; Cartapanis, Olivier; Langner, Michael; McKay, Nick; Mulitza, Stefan; Strack, Anne; Kucera, Michal (Zenodo, 2023)
This upload is an update of the PALMOD marine palaeoclimate data synthesis. It contains a synthesis of publicly availabletime series from marine sedimentary archives with benthic and planktonic foraminifera stable oxygen and carbon isotope ratios, estimates of past seawater temperature and sedimentary organic carbon, carbonate and biogenic silica content. Each time series is associated with extensive metadata and chronological information and comes along with 1,000 posterior realisations of the age-depth model. For a detailed description of the synthesis procedure, structure andcontents see the paper describing the previous version. The data are made available as a zip file, which contains 315 files in*.RDS format. They canread with the open source software R . Each file contains the data from a single sediment coreand consists of a list with relevant metadata, climate data and chronological information. The synthesis work was supported through funding by the German Ministry of Science and Education within the framework of the German Climate Modelling initiative PALMOD . Please cite the original data contributors -references provided - when using this product.